2020
DOI: 10.1007/s42452-020-3177-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of proton exchange membrane fuel cell’s end plates

Abstract: In this study, we present the optimization of end plates to produce uniform pressure and low content on the gas diffusion layer in polymer membrane fuel cell. For this purpose the end plates and the influence of parameters on the gas diffusion layer pressure has been investigated. Parameters studied are the thickness of the end plate, the depth of the bipolar plates groove and the clamping pressure applied to the end plates. After defining their values in the Abaqus finite element software, mechanical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…An analysis determining the knowledge base performed for the Polish Hy Strategy has provided the research results shown below. The research process w ried out in April and May 2021 and consisted of steps including extensive cons with stakeholders in expert panels (about 100 experts-including both domestic eign), in-depth interviews (16) and a survey on a sample of 30 specialists. The stud scope, covered all of the elements of the hydrogen economy value chain-pro storage, transport, distribution and use of hydrogen.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…An analysis determining the knowledge base performed for the Polish Hy Strategy has provided the research results shown below. The research process w ried out in April and May 2021 and consisted of steps including extensive cons with stakeholders in expert panels (about 100 experts-including both domestic eign), in-depth interviews (16) and a survey on a sample of 30 specialists. The stud scope, covered all of the elements of the hydrogen economy value chain-pro storage, transport, distribution and use of hydrogen.…”
Section: Figurementioning
confidence: 99%
“…The first generation of this drive reached a value of about 3 kW/dm 3 (MY2014), while the second generation was at 4.4 kW/dm 3 (MY2020; these values include end plates-the values may be higher otherwise). End plates play a critical role in the overall process of fuel cell optimization, as evidenced, for example, by the work of Habibnia et al [16]. Current density in subsequent generations of Toyota Mirai propulsion was increased by 15% [17].…”
Section: Fuel Cell Testing For Automotive Applicationsmentioning
confidence: 99%
“…18 Both the structure and operating conditions will greatly affect the fuel cell performance. 19,20 Establishing a cross-scale model and exploring the impact of a new structure design scheme on the internal performance of the fuel cell holds significant importance. 21 Therefore, a compensation flow field based on the serpentine structure is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Operation of a PEM fuel cell involves charge and ions transport, heat transfer, electrochemical reactions, and multi-phase flow. These phenomena occur in different components such as bipolar plates (BPs) ( Habibnia, Shirkhani & Tamami, 2020 ; Smitha, Sridhar & Khan, 2005 ), gas flow channels (GFCs) ( Djilali, 2007 ), and membrane electrode assembly (MEA) ( Wang, Basu & Wang, 2008 ). MEA consists of the catalyst layers (CLs), membrane and gas diffusion layer (GDL), and micro-porous layer (MPL).…”
Section: Introductionmentioning
confidence: 99%